Dental conditions in patients with medically unexplained oral symptoms - Mitsuhiro Asami; Yasuyuki Kimura; Miho Takenoshita; Risa Tominaga; Chizuko Maeda; Chihiro Takao; Motoko Watanabe; Trang Thi Huyen Tu; Takahiko Nagamine; Akira Toyofuku (Elsevier, 2023)
Background/purpose: Dentists sometimes struggle with treating patients with unexplained symptoms, known as oral psychosomatic disorders, that do not improve with conventional treatment. Oral psychosomatic disorders do not fit the definition of psychosomatic diseases in internal medicine. To ensure appropriate dental treatment, it is important for general dentists to distinguish between oral psychosomatic disorders and psychosomatic diseases. However, relevant evaluation methods have not yet been developed. The DMFT index is widely used as an indicator of the caries status. The purpose of this study was to compare the DMFT index scores of patients with oral psychosomatic. Materials and methods: The DMFT scores of 2202 patients with oral psychosomatic disorders, 145 psychiatric inpatients, and 3940 general dental patients were statistically compared. The DMFT of patients with oral psychosomatic disorders was further compared based on the presence or absence of psychiatric history and disease. Results: The median DMFT scores of oral psychosomatic disorder patients, psychiatric inpatients, and general dental patients were 16, 22, and 10, respectively, showing a significant difference. No significant differences were found in the DMFT scores based on the presence or absence of psychiatric history in oral psychosomatic disorder patients. Conclusion: The intraoral environment of patients with oral psychosomatic disorders was worse than that of general dental patients but better than that of psychiatric inpatients. General dentists could suspect psychiatric and oral psychosomatic disorders based on the state of patients' oral environment.